Escribimos una receta - Linares Gálvez, Nora Malena (2019)
This sufficiency job has been elaborated for children of the second grade of primary education at "Juan Velasco Alvarado" educational institution of Trujillo city in the year 2019, with the subject titled "We write recepies", in which it is given to know that learning and writing in children's age is very important, since they improve the language, both expressive and comprehensive. In addition, it also benefits them in their memory capacity, because improve the ability to remember._x000D_ About session preparation it has been worked with the didactic processes of the Communication area of the competition: Write texts written in their mother tongue to promote significant learning._x000D_ Strategies used were designed to promote the active and meaningful participation of all_x000D_ students. It is intended all the time to kindle student interest in and motivate the student for the production of written texts in the area of Communication, since it is a very important area that point for students to develop communication skills